Audit Pricing, Legal Liability Regimes, and Big 4 Premiums: Theory and Cross‐country Evidence* - Choi, Jong‐Hag; Kim, Jeong‐Bon; Liu, Xiaohong; Simunic, Dan A. (Contemporary Accounting Research, 2008)
In this paper, we first develop a model in which national legal environments play a crucial role in determining auditor effort and audit fees. Our model predicts that: (1) audit fees increase monotonically with the strength or strictness of a country’s legal liability regime; (2) given a legal liability regime, Big 4 auditors charge higher audit fees than non-Big 4 auditors; and (3) the Big 4 fee premium decreases as a country’s legal regime shifts from a weak to a strong regime. We then test the model’s predictions using a large sample of audit clients from 15 countries with different legal regimes where audit fee data are publicly available. The results of our cross-country regressions strongly support the above three predictions, and are robust to a variety of sensitivity checks. Furthermore, we find that the effects of a legal regime on audit pricing and the Big 4 premium are more salient for the small client segment than for the large client segment. Overall, our regression results indicate that a country’s legal environment plays an important role in determining both audit fees and the fee spread between Big 4 and non-Big 4 auditors.